The jungle book [videorecording (DVD)] (Disney DVD., 2014)
Meet the most unforgettable characters and embark on a thrilling adventure with Mowgli as he journeys deep into the jungle and learns 'The Bare Necessities' of life from happy-go-lucky Baloo the bear. Meet Bagheera, the wise old panther, and crazy King Louie, the orangutan. But watch out for the cunning tiger Shere Khan and Kaa, the sneakiest snake in the jungle! It is an extraordinary adventure and a heartwarming tale that celebrates the true meaning of friendship.